Caricom beyond thirty : charting new directions : Chairman's perspective - Patterson, P. J. ([s.n.] KingstonJM, 2003)
Focuses on ways of recommitting to the fundamental aims and mission of CARICOM. Looks at regional political governance and the institutional machinery of the Community. Suggests selected areas for advancing CARICOM integration.